Analisis Laporan Realisasi Anggaran Untuk Mengukur Kinerja Keuangan Pada Pemerintah Kota Bandung - Rizka Amanda; Khozin Arief; Jouzar Farouq Ishak (Indonesian Accounting Research Journal, 2021)
This study aims to determine the financial performance of the Bandung City Government in 2017 – 2020. The research method is used descriptive quantitative by measuring the level of financial ratios. The ratios are effectiveness, efficiency, independence, compatibility, and growth. The data obtained comes from the Bandung City Government Budget Realization Report document from 2017 - 2020. The results of the research show that the effectiveness ratio level of PAD receipts in Bandung City is quite effective, the level of efficiency ratio is still above 80% indicating that financial performance is less efficient, the level of independence ratio in a period of 4 years has decreased from delegative to participatory one, the level of compatibility ratio of the allocation of funds is still prioritizing operating expenditure over capital expenditure, the financial growth ratio rate from 2017 – 2019 experienced positive and negative growth, but growth for 2020 all aspects of APBD experienced negative growth due to the Covid-19.